FRIZZY PANICLE defines a regulatory hub for simultaneously controlling spikelet formation and awn elongation in bread wheat. Issue 2 (8th May 2021) - Du, Dejie; Zhang, Dongxue; Yuan, Jun; Feng, Man; Li, Zhaoju; Wang, Zihao; Zhang, Zhaoheng; Li, Xiongtao; Ke, Wensheng; Li, Renhan; Chen, Zhaoyan; Chai, Lingling; et al.
Summary: Grain yield in bread wheat ( Triticum aestivum L.) is largely determined by inflorescence architecture. Zang734 is an endemic Tibetan wheat variety that exhibits a rare triple spikelet (TRS) phenotype with significantly increased spikelet/floret number per spike. However, the molecular basis underlying this specific spike morphology is completely unknown. Through map‐based cloning, the causal genes for TRS trait in Zang734 were isolated. Furthermore, using CRISPR/Cas9‐based gene mutation, transcriptome sequencing and protein–protein interaction, the downstream signalling networks related to spikelet formation and awn elongation were defined. Results showed that the null mutation in WFZP‐A together with deletion of WFZP‐D led to the TRS trait in Zang734. More interestingly, WFZP plays a dual role in simultaneously repressing spikelet formation gene TaBA1 and activating awn development genes, basically through the recruitments of chromatin remodelling elements and the Mediator complex. Our findings provide insights into the molecular bases by which WFZP suppresses spikelet formation but promotes awn elongation and, more importantly, define WFZP‐D as a favourable gene for high‐yield crop breeding.